Power and Authority Pasca Penggabungan Satuan Polisi Pamong Praja dan Pemadam Kebakaran Kabupaten Bungo - Mulia Jaya; Sadri Sadri; Willyan Willyan; Sri Zul Chairiyah (Universitas Muara Bungo, 2023)
Power and Authority (Power and Authority) after the merger of the Civil Service Police Unit and the Fire Department. Through Bungo Regent's Regulation Number 5 of 2016 concerning the Formation and Structure of Regional Apparatus, referring to Government Regulation Number 18 of 2016 which states that if a government affair does not meet the requirements to form a Regional/Regency Service then the Government affairs can be merged. The formulation of the problem in this research is first, what is the power and authority of leaders after the merger between Pol PP and Damkar units. Second, the obstacles and efforts after the merger between Sat Pol PP and Damkar. The benefits of this research are first, to provide references and academic studies to policy makers in Bungo Regency. Second, provide knowledge about policy development in the field. The object of this research was carried out at the Civil Service Police Unit and the Bungo Regency Fire Department. Descriptive research method with a qualitative approach. The results of this research show that there is overlap and the use of power and authority in leadership is ineffective and tends to be subjective. The power and authority of leaders tends to be outside the operational standards of work tasks, giving rise to the impact of overlapping work. The obstacles faced are regarding the budget, the minimal budget provided by the regional government and the absence of education and training which has an impact on employee performance. The power and authority of leaders in giving orders or tasks should be in accordance with standard operational procedures that have been determined by regulations. legislation